The experience of structural burden for culturally and linguistically diverse family carers of people living with dementia in Australia. (22nd May 2022) - Gilbert, Andrew Simon; Antoniades, Josefine; Croy, Samantha; Thodis, Antonia; Adams, Jon; Goeman, Dianne; Browning, Colette; Kent, Mike; Ellis, Katie; Brijnath, Bianca
Abstract: Evidence suggests that family carers of culturally and linguistically diverse (CALD) people living with dementia experience higher stress and unmet need than the general Australian population. These disparities are often framed as the result of CALD communities failing to seek formal support. Challenging this, we draw on the concept of 'structural burden' to explore how the complexity of health and aged systems contribute to the burden that CALD carers experience. We conducted semi‐structured interviews with 104 family carers for CALD people with dementia in Australia, followed by thematic analysis of transcripts. Additional to structural burdens encountered by the general older population, CALD carers faced challenges understanding Australia's Anglo‐centric aged care system, locating culturally appropriate care and were required to translate the languages and operations of health and aged care systems into terms their family members understood. This burden was mitigated by the presence of ethno‐specific organisations and other navigation support. Australia's aged care system has moved towards centralised governance and consumer‐directed care provision. This system involves a confusing array of different programmes and levels, bureaucratic applications and long waiting times. Carers' encounters with these systems demonstrates how some CALD people are being left behind by the current aged care system. While ethno‐specific services can reduce this burden, not all CALD groups are represented. Consequently, improving access to dementia care among CALD populations requires entry point and navigation support that is culturally appropriate and linguistically accessible.